Utilization of Cloud Technology Applications for Efficient Office Administration among Secretaries in Rivers State Universities - Ikepu Christian Oghenerukevwe; NumbaraBari E Kayii (Training & Research Institute - Jeramba Ilmu Sukses, 2023)
The study aimed at assessing the utilization of cloud technology applications for efficient office administration among secretaries at Rivers State universities. Three research questions were posed and answered, while three corresponding hypotheses were formulated and tested at 0.05 level of significance. The research design adopted for this study is an analytic-descriptive design. The population for this study consisted of all 91 secretaries at Rivers State universities. The instrument used for data collection was the